T-cell Activation Is Correlated With Monocyte Activation in HCV/HIV Coinfection and Declines During HCV Direct-Acting Antiviral Therapy. (18th February 2021) - Auma, Ann W N; Shive, Carey; Damjanovska, Sofi; Kowal, Corinne; Cohen, Daniel E; Bhattacharya, Debika; Alston-Smith, Beverly; Osborne, Melissa; Kalayjian, Robert; Balagopal, Ashwin; Sulkowski, Mark; Wyles, David; et al.
Abstract: Background: Immune activation markers associate with morbidity and mortality in HIV and hepatitis C virus (HCV) infection. We investigated how T-cell and monocyte activation are related over the course of HCV direct-acting antiviral (DAA) therapy during HCV/HIV coinfection. Methods: Peripheral blood mononuclear cells from AIDS Clinical Trials Group (ACTG) A5329 participants and a single-site separate cohort treated with DAAs were analyzed for central memory (CM)/effector memory (EM) T-cell subsets, monocyte subsets, and cell activation (CD38 and HLA-DR expression) before, during, and after therapy. Results: Before therapy, classical and inflammatory monocyte subset HLA-DR expression positively correlated with absolute counts and frequencies of CD38 + HLA-DR + -expressing CD4 + and CD8 T cells and corresponding CM and EM subsets. After therapy initiation, CD38 + HLA-DR + co-expression on CD4 + and CD8 + memory T cells decreased by 12 weeks and 36 weeks, and plasma sCD14 positively correlated with CD38 + HLA-DR + CD4 + and CD4 + CM T-cell frequencies. Monocyte subset activation remained similar over time. Conclusions: During HCV/HIV coinfection, memory T-cell activation is associated with monocyte subset activation, consistent with related underlying mechanisms. Following therapy initiation, memory T-cell, but not monocyte, activation decreased. Residual CD4 + T-cell activation after therapy completion is associated with sCD14, potentially linking the remaining CD4 + T-cell activation to residual factors driving activation in antiretroviral therapy–controlled HIV.